(untitled) (Journal of the College of Basic Education, 2022)
Advertising display methods developed in the third millennium as a result of technological progress and the integration of computers with modern communication technologies such as satellites and the international information network. This was pointed out by the world of communication Marshall McLuhan, hence the justification for choosing the topic, as there are interactive advertising offers presented on the International Information Network, and other interactive environmental ones, and others that also use modern technologies and employ the human element to be closer to the recipient. From here came the research problem in determining the uses of patterns of interactive advertisements. The importance of the research came through the importance of the topic as it relates to a modern topic commensurate with the developments of the times in the third millennium, which is the topic of interaction, participation and exchange of opinion and knowledge of the desires and needs of the public. The aim of the research is to identify the use of patterns of interactive network and tablet advertisements and the employment of the human personality. The current research followed the descriptive analytical approach to study the phenomenon and various models were analyzed that surrounded modern interactive advertising types. As for the most important means of data collection, a form was prepared for this purpose. The most important conclusions were: Modern technological systems and their continuous developments have contributed to creativity and innovation of new methods and ways of interacting with the individual in providing a service, commodity or product in a manner commensurate with the developments of technological eras. Technology has become important in shaping the user’s interactive experience because it enables him to reach his goals in purchasing, services or information. The technical structure of commercial advertisements is important in achieving interactivity through the mechanisms of mobility, participation, interaction and the technical construction of network advertising and interactive tablet advertisements, so it must be in accordance with a coordinated visual system in order not to confuse the user in accessing the product or service. The most important recommendations:- The necessity of paying attention to technology, because it has become one of the basic requirements in human life in the third millennium and has entered into various aspects of the life of the individual, including advertisements of all kinds. The necessity of creativity and the discovery of new technological methods for the interaction of the individual and keeping pace with the developments of the times in a way that serves the society and the individual together.